1975
DOI: 10.1083/jcb.64.1.223
|View full text |Cite
|
Sign up to set email alerts
|

Actin associated with membranes from 3T3 mouse fibroblast and HeLa cells.

Abstract: A protein component of membranes isolated from 3T3 mouse fibroblasts and HeLa cells has been identified as actin by peptide mapping. Extensive but apparently not total coincidence was found between the peptide maps of these two nonmuscle membrane-associated actins compared to chick skeletal muscle actin. Between 2 and 4% of the total membrane protein appears in the actin band on sodium dodecyl sulfate polyacrylamide gels of 3T3 membranes while about 4% of the membrane protein appears as the actin band from HeL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

1975
1975
1984
1984

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(42 citation statements)
references
References 42 publications
(30 reference statements)
1
41
0
Order By: Relevance
“…The plasma membrane fraction of HeLa cells contains a concentrated form of HMWP (11,35), and actin-binding protein has been reported to be present in macrophage plasma membranes (21) and the cortical blebs released from macrophages by sonication (6). The recent observation of actinbinding protein by immunofluorescence techniques on phagolysosomes of polymorphonuclear leukocytes (3) suggests that it (or HMWP) is located on the inner surface of the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma membrane fraction of HeLa cells contains a concentrated form of HMWP (11,35), and actin-binding protein has been reported to be present in macrophage plasma membranes (21) and the cortical blebs released from macrophages by sonication (6). The recent observation of actinbinding protein by immunofluorescence techniques on phagolysosomes of polymorphonuclear leukocytes (3) suggests that it (or HMWP) is located on the inner surface of the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The present observations, showing a concomitant inhibition of gelation and specific disaggregation of both actin and HMWP by CB, provide additional evidence for the specific role of actin and HMWP in gelation of cytoplasmic extracts. We previously reported that actin is present and H M W P is concentrated in the plasma membrane fraction of HeLa cells (10), and that both actin and the H M W P can be enriched in a precipitate 1.2 fraction of a suitable extract of the plasma mem- 1.0 brane (37). These results indicate that actin and _g H M W P from plasma membrane or whole cell ~ o.a extracts undergo similar interactions.…”
Section: Discussionmentioning
confidence: 99%
“…HeLa cells, grown as described (10,37), were collected at room temperature by low-speed centrifugation and washed once with 20 vol of cold 0.1 M NaCl. All subsequent operations were carried out at 0-4~ Cells were suspended in 2 vol (based on the packed cell volume before washing) of 0.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the interwoven network that has been so elegantly described by Buckley and Porter (4) in preparations of tissue culture cells that were fixed, critically point dried, and examined with high voltage microscopy may in fact be actin and its associated proteins. It may also be no coincidence that when the plasma membrane fraction of cultured cells, namely HeLa cells, is run by SDS-gel electrophoresis, not only is actin present (8), but also there is a pair of bands whose molecular weights resemble that of the proteins associated with the actin in sperm. Similar proteins are present in myoblasts, chrondroblasts (my unpublished observations), and human erythrocytes (40).…”
Section: Discussionmentioning
confidence: 99%